Research Progress of Traditional Chinese and Western Medicine in Mastitis During Non-lactation Period - Shi, Yuanyuan; Li, Zhi; Chen, Xuan; Hu, Jinchuan; Xiao, Yushan (Journal of Contemporary Medical Practice, 2025)
Non-lactating mastitis is a group of benign and non-specific inflammatory diseases of unknown etiology that occur in women during the non-lactation period, including mammary ductal ectasia/periductal mastitis, granulomatous lobular mastitis. In recent years, the incidence of this disease has shown a significant upward trend, although it is a group of benign diseases, but it seriously affects the quality of life, causing harm to the physical and mental health of the majority of women, and it is of great research significance to explore the treatment of non-lactating mastitis with traditional Chinese and Western medicine.